Pulse wave shapes characterisation in nonthermal pulse electric field method for food preservation - Kasri, Nur Faizal (2023)
Pulsed Electric Field (PEF) is a technique that does not use any heating element in inactivating food borne pathogens and spoilage microorganisms. The advantage of this technique is that it can preserve the physical properties of food, such as colour, flavour, and nutritional value while extending its shelf life. With the straightforward working principle and well-known advantages, this technique can replace the traditional method for food pasteurisation which uses heat. However, existing PEF devices lack several features: low voltage amplitude, limited control of pulse properties, and expensive besides no optimal range of treatment parameters clearly defined for specific foods. These shortcomings limit their function in the subset of pulse applications. Therefore, this study was conducted to fill the available innovation space to solve or at least reduce the shortcomings in PEF devices today. In this thesis, a compact high-voltage pulse generator was developed by implementing the concept of capacitor discharge to produce a square pulse (mono polar fashion) to inactivate microbes inherently in raw goat’s milk. The development phase began with a simulation study regarding the design of a compact high voltage pulse generator circuit and a treatment chamber that produced the desired results. Then, it was tested practically on sodium chloride (NaCl) solution with the conductivity of 100 mS/m, and the result was the same as the simulation with few insignificant differences. From the experiments performed on raw goat’s milk, the results obtained suggest that a frequency of 10 Hz, a voltage amplitude of 4 kV, and a pulse width between 1 – 4 µs promise the best results in the treatment process. The inherent microorganisms have been successfully reduced from 2.98 × 106 Colony Forming Unit (CFU)/ml to 1.64 × 106 CFU/ml, an almost 60% reduction or 0.55 survival ratio. This thesis also suggests that the compact high-voltage pulse generator has a vast potential to inactivate other types of microorganisms in various kinds of liquid food. This is due to the flexibility and reliability offered by the compact high voltage pulse generator developed in this study.